When Syntax and Stylistics Meet in â€œAubreyâ€ - Ahmad IdrisAsmaradhani (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2013)
AbstractThe language of songs can be seen as one of the results of the ever-changing system of language itself. In linguistic views, the language of songs is often seen as similar to the language of poems. That is, in the language of songs, the composers formulate some expressions to describe diverse experiences. Perhaps one of the most significant evolutionary changes of language system is the introduction of the new meaning(s) of a word as its internal states and its relationships to other words. The relationship between one word with anotherâ€”strung both syntactically and stylisticallyâ€”can produce meaningful strings and are capable of stimulating extra meanings. Applying the theories of syntax and stylistics, this paper is intended to analyze how some expressions in the song â€œAubreyâ€ offer some possible extra logical meanings and make it a very popular song in the 70s up to the present day.Â Keywords: extra logical meaning, metaphor, senses